Pengaruh Gaya Kepemimpinan dan Motivasi Kerja terhadap Loyalitas Pegawai pada Kantor Kecamatan Bungku Pesisir - Misrawati Misrawati; Yoberth Kornelius (Public Service and Governance Journal, 2026)
This study aims to analyze the influence of leadership style and work motivation on employee loyalty at the Bungku Pesisir District Office, Morowali Regency. The study used a quantitative approach by distributing questionnaires to 40 employees as respondents. The research instrument consisted of 36 statement items with the variables of leadership style (X1), work motivation (X2), and employee loyalty (Y). The data were analyzed using descriptive statistics, classical assumption tests, and multiple linear regression analysis. The results of the descriptive analysis showed that leadership style and work motivation were in the high category, while employee loyalty was also classified as very good. Normality, multicollinearity, and heteroscedasticity tests showed that the regression model met the requirements of the analysis. The results of multiple linear regression showed that leadership style and work motivation had a positive and significant effect on employee loyalty, both partially and simultaneously. A determination coefficient (R²) of 0.725 showed that 73% of employee loyalty variations were influenced by these two independent variables, while the other 27% were influenced by other factors outside the study. Thus, this study concludes that improving effective leadership style and strong work motivation play an important role in strengthening employee loyalty in the Bungku Pesisir District Office. The results of this study imply that organizations need to improve the quality of leadership and create a work environment that can motivate employees optimally.